Discourse on Rejection of Women Leader in Yogyakarta ; Critical Discourse Analysis of Kompas Daily News - Catur Nugroho; Wisma Nugraha Christianto Richardus; Sugeng Bayu Wahyono (Jurnal Pekommas, 2021)
The phenomenon of power in Yogyakarta attracted the attention of various groups, including the national media when differences of opinion emerged regarding the requirements for candidates for Governor and Deputy Governor candidates of the Special Region of Yogyakarta. The Governor of Yogyakarta is directly held by the Sultan as the King of the Yogyakarta Palace in accordance with the Yogyakarta Privileges Law. The problem arose when Sultan HB X did not have a son, and some parties interpreted the special law and regional regulations requiring that the governor of Yogyakarta be held, male. This problem has attracted the national media to produce news texts related to the pros and cons of women leaders in Yogyakarta. This research intends to uncover how the national media of Kompas daily constructs discourses on the rejection of female leaders and how the struggle for public acceptance or ideological ideas related to leadership succession in Yogyakarta. With a qualitative approach, the method used in this study is Norman Fairclough's Critical Discourse Analysis model. News texts related to the issue of leadership succession were analyzed starting from the text level, discourse level, and sociocultural level. The results of the study found that the production of the Kompas daily news text in practice represents a group that rejects female leaders in Yogyakarta. Local political elites in parliament, Keraton aristocrats, and Sultan HB X mutually defend their views on women's rights to become leaders in Yogyakarta. Kompas Daily provides a space for discourse on the issue of women's rejection to represent their side of those who reject women leaders